Fuzzy multiple criteria assessment of construction site alternatives for non-hazardous waste incineration plant in Vilnius city, applying ARAS-F and AHP methods - Turskis, Zenonas; Lazauskas, Marius; Zavadskas, Edmundas Kazimieras (Journal of Environmental Engineering and Landscape Management, 2012)
Continuous increase in electricity and heat prices for citizens necessitates new alternative solutions regarding rational application of existing resources, in order to minimize electric energy production costs. The article presents the description of waste incineration plant siting issue, related to satisfaction of requirements formulated by investors, citizens, contractors and other concerned parties. As the siting process represents fulfilment of the above-stated stakeholder requirements, the multiple criteria task is defined. Seven local assessments of alternative sites located in densely populated urban and industrial development areas have been evaluated. The results of calculations show that the above industrial equipment units cover economic, social and environmental aspects. It was found that the most appropriate place for construction of waste incineration plants is the Paneriai industrial area. Densely populated urban districts can be referred to as the most improper location for waste incineration. The best results can be gained applying complex AHP and ARAS-F methods.Article in English.Statybvitės parinkimo nepavojingų atliekų deginimo įmonei Vilniuje variantų vertinimas AHP Ir ARAS-F metodaisSantrauka. Nuolat didėjančios gyventojų vartojamos elektros ir šilumos energijos kainos verčia ieškoti alternatyvių sprendimų racionaliau naudoti turimus išteklius – mažinti energijos gamybos išlaidas. Nagrinėjama statybvietės būsimai atliekų deginimo įmonei parinkimo problema. Jos sprendimas susijęs su investuotojų, gyventojų, rangovų ir kitų suinteresuotųjų grupių poreikiais. Parenkant vietą siekiama atsižvelgti į šių grupių pageidavimus, todėl formuluojamas daugiakriteris uždavinys. Vertinamos septynios tam parinktų vietų miesto pramonės plėtros ir tankiai gyvenamose teritorijose alternatyvos. Skaičiavimų rezultatai rodo, kad tokio tipo pramonės objektų kūrimas susijęs su ekonominiais, socialiniais ir aplinkosaugos veiksniais. Nustatyta, kad tinkamiausia vieta atliekų deginimo įmonei statyti yra Panerių pramoninis rajonas. Netinkamiausia atliekoms deginti vieta yra tankiai apgyventi miesto mikrorajonai. Geriausio rezultato paieškai taikomas kompleksinis sprendimas AHP ir ARAS-F metodais.Reikšminiai žodžiai: atliekų deginimas, alternatyvioji energija,  AHP ir ARAS-F metodai, statybvietės parinkimas, atliekų tvarkymo technologijos